Biochemistry of oceanic plankton and chemical composition of plankton from different depths of the Northwestern Pacific. - Vinogradov, Mikhail E; Bordovsky, Oleg K; Akhmet'yeva, E A (PANGAEA, 1970)
Determinations were made of contents of carbon, lipids, nitrogen and, in some material, protein, carbohydrates, elementary composition of lipids and their spectral composition in total plankton samples from different depths (from the surface to 3000 m) and in several species of macroplanktonic deep-water crustaceans (decapods and mysids) living at different depths. Content of organic carbon and lipids in total plankton is high (40 to 60 and 35 to 70% of dry weight, respectively) and it does not change significantly with increasing depth. Deep-water macroplanktonic crustaceans have extremely high content of organic carbon and lipids, but there are no significant differences in this respect between species that live in different layers of the deep-water zone. Elementary composition of lipids indicates that they are highly saturated, with a marked predominance of unsaponifiable fraction, about 20% of which consists of methane hydrocarbons.
(Table 1) Vertical distribution of relative contents of the main planktonic groups in the water column of the Kuril-Kamchatka region at Station VITYZ5635
Keywords: Archive of Ocean Data; ARCOD; Chaetognatha; Copepoda; Counting, Binocular microscope; Decapoda; DEPTH, sediment/rock; Euphausiacea; JUDAY; Juday net; Mysidacea; Northwest Pacific; VITYAZ; Vityaz (ex-Mars); VITYAZ5635